Plant-Based Milks: Almond - Elena Torna; Daniela Rivero-Mendoza; Wendy Dahl (EDIS)
Almond milk, a plant-based milk alternative, is produced from almonds and water. Almond milk originated from the Mediterranean region and has been consumed for many years. In the United States, there are several marketed brands of almond milk. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department describes the nutrient profile and potential health benefits and risks of almond milk. Written by Elena Torna, Daniela Rivero Mendoza, and Wendy J. Dahl. https://edis.ifas.ufl.edu/fs410